Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations getting up early enough to visit the lavatory before, or after, breakfast. If such simple measures do not produce the desired result, it is high time to consult a doctor. Quack medicines are worse than useless, and may do harm by removing the symptoms while the cause is really getting steadily worse. [illustration] Consult a doctor — Quack medicines are worse than useless TOILET HINTS For your bath. — Dissolve two tablespoonfuls of starch in a small basin of water and add to your big bath. Starch is soothing to the skin when it is inclined to be irritable with heat or overtiredness. Cucumber lotion is soothing in sunny weather, and can be made from the ends left over from a salad. Mince it up, just cover with milk and steam it in an egg-cup for 20 minutes. When cool dab it on the face and hands with clean tufts of cotton-wool. Flushing of the face. — Avoid, very hot drink and drinking quickly. Keep calm and quiet, try not to think about the flushing, and the habit will soon leave you. Red arms. — Put a handful of oatmeal in your washing water and lave your arms with it, afterwards rubbing in cold cream. Greasy skin. — Lemon juice and water, one part to two, dabbed on the skin, is excellent, but wash your face thoroughly first. Drink plenty of cold water. 23 177/5/8/4